The Hermeneutics of the Qur’an: A Comparative Study of Fazlur Rahman and Nasr Hamid Abu Zayd - Mohammad Muslih; Ahmad Hisyam Syamil; Amir Reza Kusuma (Penerbit Hellow Pustaka, 2025)
This study examines the hermeneutical approaches of Fazlur Rahman and Nasr Hamid Abu Zayd in interpreting the Qur’an, highlighting their methodological innovations and epistemological divergences. Fazlur Rahman’s